The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1109/ojies.2022.3149333
|View full text |Cite
|
Sign up to set email alerts
|

Imitation Learning for Variable Speed Contact Motion for Operation up to Control Bandwidth

Abstract: The generation of robot motions in the real world is difficult by using conventional controllers alone and requires highly intelligent processing. In this regard, learning-based motion generations are currently being investigated. However, the main issue has been improvements of the adaptability to spatially varying environments, but a variation of the operating speed has not been investigated in detail. In contact-rich tasks, it is especially important to be able to adjust the operating speed because a nonlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Bilateral control-based imitation learning has been proposed as a method that can compensate for this control delay [16], [17]. We indicated that this method can generate variable speed motions that consider the dynamics between the robot and environment [18], [19]. Although this method is expected to enable nonprehensile manipulations at high speed and multiple speeds, it is difficult to learn complex dynamics between objects and the environment from sensor data and requires a significant amount of training data.…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral control-based imitation learning has been proposed as a method that can compensate for this control delay [16], [17]. We indicated that this method can generate variable speed motions that consider the dynamics between the robot and environment [18], [19]. Although this method is expected to enable nonprehensile manipulations at high speed and multiple speeds, it is difficult to learn complex dynamics between objects and the environment from sensor data and requires a significant amount of training data.…”
Section: Introductionmentioning
confidence: 99%
“…Automation of tasks with changing contact states, such as assembly and grinding, which are called contact-rich tasks, are widely studied in robotics [1]- [4]. In contact-rich tasks, the contact force with the environment changes significantly depending on the contact states; hence, force-sensing methods for detecting contact force are important.…”
Section: Introductionmentioning
confidence: 99%